The evolution of the State Immunity Law in the light of the case Germany v. Italy (2): where do we stand? - Fazzini, Anna (Diritto Pubblico Europeo - Rassegna online, 2023)
The contribution deals with the complex issue of State immunity from foreign civil jurisdiction in case of State conducts resulting in serious violations of human rights and humanitarian law. In particular, in light of the new appeal Germany v. Italy brought before the International Court of Justice (ICJ) on 29 April 2022, the possible future scenarios of which will be here assessed, the current state of development of the immunity rule and the contribution made to this end by the Italian case law Ferrini-Judgment 238/2014 will be questioned. The latter will be assessed from multiple perspectives, namely in relation to the contribution made 1) to the development of the customary rule of immunity, 2) to the practice of invoking constitutional principles as a circumstance precluding wrongfulness, and 3) to the formation of a specific international norm protecting the right to justice. Considering this assessment, although the rule of State immunity is still widely supported by the international community, the contribution argues that there are important jurisprudential developments and solid legal arguments in support of a limitation based on the protection of fundamental human rights, which the ICJ should not ignore when re-evaluating the rule of immunity in a possible new ruling